Strategi Kepemimpinan Kepala Madrasah dalam Meningkatkan Kualitas Kelembagaan Menghadapi Era 4.0 di MTs Sholatiyah Petir Serang - Uun Yuliatinupus; Muslihun Muslihun; Ashari Ashari (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This research aims to identify institutional quality, quality improvement strategies, and obstacles faced in the implementation of strategies at MTs Sholatiyah Petir Serang in the 4.0 era. The main focus of the research includes three aspects, namely: 1) institutional quality at MTs Sholatiyah Petir Serang, 2) strategies implemented by madrasah heads to improve institutional quality, and 3) obstacles faced in the implementation of these strategies. The results of the study show that the institutional quality at MTs Sholatiyah Petir Serang has advantages in developing students' character, applying religious values, and utilizing technology in learning activities. However, challenges still arise in terms of human resource management, limited infrastructure, and the ability of teachers and education staff to the rapid development of educational technology. The strategies implemented by madrasah heads in improving institutional quality include the implementation of needs-based personnel management, improving teacher competence through continuous training, optimizing the use of technology in teaching and learning activities, and creating a conducive, collaborative, and competitive school environment. The main obstacles faced include the limited mastery of new technologies, lack of financial resources and infrastructure, and the urgent need for adaptive and innovative leadership. The findings of this study confirm the importance of effective, flexible, and needs-oriented strategies in the 4.0 era in managing educational institutions. By optimizing the quality improvement strategy and overcoming various obstacles, MTs Sholatiyah Petir Serang has the potential to improve institutional quality while strengthening its role as a madrasah that is relevant to the demands of the times.